Comparative Transcriptional Profiling of Primed and Non-primed Rice Seedlings under Submergence Stress - Hussain, Saddam; Yin, Hanqi; Peng, Shaobing; Khan, Faheem A.; Khan, Fahad; Sameeullah, Muhammad; Hussain, Hafiz A.; Huang, Jianliang; Cui, Kehui; Nie, Lixiao (Frontiers in Plant Science, 2016)
Submergence stress is a limiting factor for direct-seeded rice systems in rainfed lowlands and flood-prone areas of South and Southeast Asia. The present study demonstrated that submergence stress severely hampered the germination and seedling growth of rice, however, seed priming alleviated the detrimental effects of submergence stress. To elucidate the molecular basis of seed priming-induced submergence tolerance, transcriptome analyses were performed using 4-day-old primed (selenium-Se and salicylic acid-SA priming) and non-primed rice seedlings under submergence stress. Genomewide transcriptomic profiling identified 2371 and 2405 transcripts with Se- and SA-priming, respectively that were differentially expressed in rice compared with non-priming treatment under submergence. Pathway and gene ontology term enrichment analyses revealed that genes involved in regulation of secondary metabolism, development, cell, transport, protein and metal handling were over-represented after Se- or SA-priming. These coordinated factors might have enhanced the submergence tolerance and maintained the better germination and vigorous seedling growth of primed rice seedlings. It was also found that many genes involved in cellular and metabolic processes such as carbohydrate metabolism, cellular and metabolic biosynthesis, nitrogen compound metabolic process, transcription and response to oxidative stress were induced and overlapped in seed priming treatments, a finding which reveals the common mechanism of seed priming-induced submergence tolerance. Taken together, these results may provide new avenues for understanding and advancing priming-induced responses to submergence tolerance in crop plants.